If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x + -5) + -1ln(x + 2) = ln(x + -10) + -1ln(x + 10) Reorder the terms: ln(-5 + x) + -1ln(x + 2) = ln(x + -10) + -1ln(x + 10) (-5 * ln + x * ln) + -1ln(x + 2) = ln(x + -10) + -1ln(x + 10) (-5ln + lnx) + -1ln(x + 2) = ln(x + -10) + -1ln(x + 10) Reorder the terms: -5ln + lnx + -1ln(2 + x) = ln(x + -10) + -1ln(x + 10) -5ln + lnx + (2 * -1ln + x * -1ln) = ln(x + -10) + -1ln(x + 10) -5ln + lnx + (-2ln + -1lnx) = ln(x + -10) + -1ln(x + 10) Reorder the terms: -5ln + -2ln + lnx + -1lnx = ln(x + -10) + -1ln(x + 10) Combine like terms: -5ln + -2ln = -7ln -7ln + lnx + -1lnx = ln(x + -10) + -1ln(x + 10) Combine like terms: lnx + -1lnx = 0 -7ln + 0 = ln(x + -10) + -1ln(x + 10) -7ln = ln(x + -10) + -1ln(x + 10) Reorder the terms: -7ln = ln(-10 + x) + -1ln(x + 10) -7ln = (-10 * ln + x * ln) + -1ln(x + 10) -7ln = (-10ln + lnx) + -1ln(x + 10) Reorder the terms: -7ln = -10ln + lnx + -1ln(10 + x) -7ln = -10ln + lnx + (10 * -1ln + x * -1ln) -7ln = -10ln + lnx + (-10ln + -1lnx) Reorder the terms: -7ln = -10ln + -10ln + lnx + -1lnx Combine like terms: -10ln + -10ln = -20ln -7ln = -20ln + lnx + -1lnx Combine like terms: lnx + -1lnx = 0 -7ln = -20ln + 0 -7ln = -20ln Solving -7ln = -20ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '20ln' to each side of the equation. -7ln + 20ln = -20ln + 20ln Combine like terms: -7ln + 20ln = 13ln 13ln = -20ln + 20ln Combine like terms: -20ln + 20ln = 0 13ln = 0 Divide each side by '13'. ln = 0 Simplifying ln = 0 The solution to this equation could not be determined.
| -16=x-2 | | 24y+2x=48 | | 25(3)-5y=-25 | | 45x-24= | | 4x-104=180 | | 8-40=4a+60 | | 3r/1=4 | | 1.25q-12.5=8.35 | | -29b-84=b+336 | | b+11*3=-2 | | -8=4(y+1) | | (3x-8)(2x-4)= | | (-n+(-5))-(6n+(-6))= | | 8-15P=3P-10 | | 25x-5y=-25 | | 2.5x-6=-4-3.5x | | 14=x+-4+2x | | f=.50kv | | 4x-14=180 | | 9n^2=44n | | (3n+5(-5))-(2n+(-8))= | | f(x)=x^3-3x^2+3x-1 | | ln(x+1)=1.2+ln(x) | | -9=-5y+6 | | 74x=257+(-63x) | | 4u+4-54=14 | | 12=6y+12x | | 7x^2=74x | | 4u+4-54=-14 | | 5=4t+13 | | 3(2n-1)=6n-4 | | x^4+14x^2+48=0 |